2017
DOI: 10.1097/mph.0000000000000890
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler Screening in 50 Patients With Sickle Cell Hemoglobinopathies in Iran

Abstract: On the basis of our results, there was no significant difference in the mean velocity TCD values between patients with and without evidence of ischemic brain damage in brain MRI. The frequency of silent ischemia was much lower than expected. Further studies with larger sample sizes are needed to elucidate the positive predictive value of abnormal TCD in the prediction of silent ischemia in patients with sickle hemoglobinopathy in certain ethnic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…TCD can be used to detect the disease when it occurs in cerebral blood flow. Zamani et al [16] showed that TCD was better than EEG in identifying the diseased vessels, ischemic degree, and anatomical location. However, EEG may find the changes of brain wave in VBI patients from the perspective of electrophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…TCD can be used to detect the disease when it occurs in cerebral blood flow. Zamani et al [16] showed that TCD was better than EEG in identifying the diseased vessels, ischemic degree, and anatomical location. However, EEG may find the changes of brain wave in VBI patients from the perspective of electrophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…These events result in tissue ischemia, which leads to acute and chronic pain as well as damage of different organs in the body 7 . The low prevalence of ischemic change in some patients may be partly explained by the higher Hb F percentage among them 8 . The sickle cell anemia (SCA) patients with high Hb F level, Southern Iran, India and Eastern Saudi Arabia have the benign clinical course 9,10 .…”
mentioning
confidence: 99%